European and Mediterranean hydroclimate responses to tropical volcanic forcing over the last millennium. Issue 10 (27th May 2017) - Rao, M. P.; Cook, B. I.; Cook, E. R.; D'Arrigo, R. D.; Krusic, P. J.; Anchukaitis, K. J.; LeGrande, A. N.; Buckley, B. M.; Davi, N. K.; Leland, C.; Griffin, K. L.
Abstract: Volcanic eruptions have global climate impacts, but their effect on the hydrologic cycle is poorly understood. We use a modified version of superposed epoch analysis, an eruption year list collated from multiple data sets, and seasonal paleoclimate reconstructions (soil moisture, precipitation, geopotential heights, and temperature) to investigate volcanic forcing of spring and summer hydroclimate over Europe and the Mediterranean over the last millennium. In the western Mediterranean, wet conditions occur in the eruption year and the following 3 years. Conversely, northwestern Europe and the British Isles experience dry conditions in response to volcanic eruptions, with the largest moisture deficits in posteruption years 2 and 3. The precipitation response occurs primarily in late spring and early summer (April–July), a pattern that strongly resembles the negative phase of the East Atlantic Pattern. Modulated by this mode of climate variability, eruptions force significant, widespread, and heterogeneous hydroclimate responses across Europe and the Mediterranean. Key Points: We investigate volcanic forcing of spring‐summer European hydroclimate over the last millennium using three paleoclimatic reconstructions We find significant wetting over the western Mediterranean and drying over northwestern Europe up to 3 years posteruption Post eruption hydroclimate anomalies strongly resemble a negative phase of the East Atlantic Pattern